PENGARUH JOB BURNOUT DAN WORK OVERLOAD PADA KINERJA AUDITOR DENGAN EMOTIONAL STABILITY SEBAGAI PEMODERASI - Pucangan, Made Laksmi Cintya; Gayatri, Gayatri; Rasmini, Ni Ketut; Budiartha, Ketut (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.11.NO.03.TAHUN.2022DO - 10.24843/EEB.2022.v11.i03.p10, 2022)
Auditor is a profession that has certain qualifications in performing audit tasks on financial statements and activities of a company, organization, institution or agency. The purpose of this study was to obtain empirical evidence about the effect of job burnout and work overload on auditor performance and the ability of emotional stability to moderate the effect of job burnout and work overload on auditor performance. This research was conducted at the Public Accounting Firm in Bali The data was collected using questionnaires. The method of determining the sample using purposive sampling with a sample of 75 auditors at the Public Accounting Firm in Bali Province. The data analysis technique used Structural Equation Model (SEM) with Partial Least Square (PLS) software. The results of the analysis show that job burnout has a negative effect on auditor performance. Work overload has a negative effect on auditor performance. Emotional stability weakens the effect of job burnout on auditor performance, and emotional stability weakens the effect of work overload on auditor performance. The implications of this research are theoretically to confirm the relationship between attribution theory and job burnout, work overload, emotional stability, and auditor performance. The practical implications of this research are to provide input on improving the performance of auditors at Public Accounting Firms in Bali Province.